CHARACTERISTICS OF THE MODERN TAXONOMIC COMPOSITION OF PHYTOPLANKTON IN THE KAZAKHSTAN PART OF THE RIVER IRTYSH (Experimental biology, 2024)
In the summer of 2023, the species richness of planktonic algae of the Kazakh part of the Irtysh River was investigated. 153 species and subspecies of algae belonging to 86 genera and 6 phyla have been registered. Heterokonty - Heterokontophyta (69), the phylum combining diatoms, golden, brown and yellow-green algae, green - Chlorophyta (61), cyanobacteria - Cyanobacteria (16), charophytes - Charophyta (4), euglenoids - Euglenophyta (2), and dinophytes - Dinoflagellata (1). Similarity of species richness between II, III and IV sites was large, and small between I and the rest.
Keywords: phytoplankton, taxonomic structure, taxonomic similarity, genus, species, Irtysh river